Evolutionary History of Multiple Dural Fistula - Braulio Martinez-Burbano MD; Edgar Patricio Correa Diaz MD, MSc; Carolina Jácome Sánchez MD (SAGE Publishing, 2016)
Intracranial dural arteriovenous fistulas (DAVFs) are abnormal communications between arteries and veins or dural venous sinuses, which sit between the sheets of the dura. They represent 10% to 15% of intracranial vascular malformations. Clinical manifestations and prognosis depend on the pattern of venous drainage and location. The clinical presentation of DAVF may be mistaken for vascular or nonvascular brain pathologies. For that reason, within the differential diagnosis come a wide range of conditions, such as secondary headaches, encephalopathies, dementias including those with rapid progression, neurodegenerative diseases, inflammatory processes, or tumors typically at the orbital level or in the cavernous sinus. Diagnosis requires a high degree of suspicion because of the multiplicity of symptoms and presentations, making this pathology an entity that provides a major challenge for clinicians, yet early and multidisciplinary treatment of high-grade fistulas improve the possibility of avoiding poor or unfavorable outcomes for the patient.